Entomovirological investigation of mosquitoes (Diptera: culicidae) in areas with yellow fever epizootics in Goiânia, Goias, Brazil - Alves Silva, Bruno Sérgio; Alberto Santos Neves, Maycon Sebastião; Silva do Nascimento, Teresa Fernandes; da Silva Xavier, Alexandre; Pinto Nunes Neto, Joaquim; C Ilacqua, Roberto; Zorello Laporta, Gabriel; Takashi Obara, Marcos (Revista de Patologia Tropical / Journal of Tropical Pathology, 2024)
The objective of this investigation was to analyze the occurrence and natural infection of mosquitoes in areas with epizootics of non-human primates (NHP) confirmed for yellow fever in the municipality of Goiânia, Goiás, Brazil from November 2020 to April 2021. This is an ecological, descriptive, retrospective study, with quantitative and qualitative data on the mosquito fauna collected in 10 areas. A total of 2,787 Culicidae were collected and allocated in 8 genera and 23 species. Of the total specimens captured, 2,341 (84%) were females and 446 males (16%). Haemagogus janthinomys occurred in 2.7% (74) of the cases and Haemagogus leucocelaenus in 4.5% (125); Sabethes chlropterus occurred in 0.1% (3) of the cases, Sabethes albiprivus in 1% (28), and Sabethes glaucodaemon in 0.3% (8); Aedes aegypti occurred in 19.7% (548) and Aedes albopictus in 3.9% (108) of the cases. The Sa. glaucodaemon species was recorded for the first time in Goiânia. Yellow fever infection was not detected in the collected specimens. We conclude that the presence of wild vectors, in addition to potential urban vectors, enabled the classification of receptive and vulnerable areas to the circulation of the yellow fever virus. KEYWORDS: Entomological surveillance; vector mosquitoes; epizootics; yellow fever.